The pea crop : a basis for improvement - Hebblethwaite, P. D.; Heath, M. C. (Martin C.); Dawkins, T. C. K. (Tudor C. K.) (Butterworths, 1985)
The Pea Crop: A Basis for Improvement documents the proceedings of the University of Nottingham 40th Easter School in Agricultural Science, held at the School of Agriculture, Sutton Bonington, 2-6 April 1984. The aim of the conference was to formulate a basis for improving the pea crop by bringing together international scientists to present research findings and review published work on a wide range of subject areas encompassing pea genetics, plant breeding, agronomy, crop and plant physiology, utilization, and marketing. This volume contains 42 papers organized into 10 parts. Part I discusse.